Development and consumer perceptions of a snack machine producing customized or personalized on-demand bakery products - Lappi, Jenni; Arvola, Anne; Calton, Alex; Umer, Adil; Vanhatalo, Saara; Kilpeläinen, Pekka; Pennanen, Kyösti; Sozer, Nesli (Elsevier, 2025)
Vending machines typically offer unhealthy snacks but have underutilized potential to provide healthier options on demand. This paper introduces a prototype snack machine with two separate versions of function for producing either a) customized or b) personalized fresh bakery products. The development of the machine and user studies assessing its usability and added value are discussed. In the first study (n = 81), consumers evaluated food customization by adding extra protein or fiber. In the second study (n = 23), food personalization was explored through snack recommendations based on dietary preference data from an integrated personalization platform. Majority of consumers (64–91 %) in both studies had positive attitudes towards the snack machine. Usability ratings for the machine and personalization platform were favorable, with all mean scores significantly above neutral. In the first study, 62 % of participants used the customization options. The primary added value was the ease of snack acquisition compared to participants’ current situation. Fresher snacks were perceived as an advantage. In the second study, the personalization function was highly appreciated when 91 % selected the recommended snack, with 87 % finding the recommendations useful. Participants believed the machine would add value by saving time, making snack acquisition easier, offering healthier, higher-quality options, and allowing them to influence type of snacks. These findings support further development of such machines to improve access to fresh and healthy snacks, especially with the new personalization function. Larger studies involving frequent vending machine users are needed to assess commercial potential and broader applicability.
Keywords: Consumer perceptions; Snacks; Vending machine; Food customization; Food personalization; fi=Markkinointi|en=Marketing|